The Impact of Plant-Based Coatings in “ROCHA” Pear Preservation during Cold Storage: A Metabolomic Approach - Alexandre M. A. Fonseca; Cindy Dias; Ana L. Amaro; Nélson Isidoro; Manuela Pintado; Armando J. D. Silvestre; Sílvia M. Rocha (Foods, 2020)
Although new storage technologies have been emerging in recent years, preservation of pear (Pyrus communis L.) remains a challenge for suppliers. Maintenance of desired organoleptic properties throughout cold storage using non-chemical strategies has been investigated and the use of edible coatings has shown potential to delay fruit quality deterioration during cold storage. Thus, the objective of this study is to evaluate the impact of pectin coatings including plant extracts, in “Rocha” pear (Pyrus communis L. cv. Rocha) preservation. A four-month pilot scale assay was performed in both dynamic controlled atmosphere (DCA) (−0.5 °C, 0.5% O2, and 0.4% CO2) and normal atmospheric (NA) conditions (2 °C). For each storage condition, the following three coatings were tested: pectin (3% w/v) (PCT), pectin (3% w/v) + strawberry tree leaves extract (9.5 mg/mL) (CT1), and pectin (3% w/v) + apple pomace extract (16 mg/mL) (CT2). Volatile compounds, potentially related to aroma or ripening status of “Rocha” pear, were monitored alongside with conjugated trienols (CTs) and maturity parameters. The combination of DCA conditions and the application of pectin coatings were able to reduce the release of Rocha pear volatiles associated with ripening status, (particularly esters and sesquiterpenes), as well as reduce CTs, which could contribute to the preservation of Rocha pear for longer periods.